Task sharing with non-physician health-care workers for management of blood pressure in low-income and middle-income countries: a systematic review and meta-analysis - T N Anand, MPH; Linju Maria Joseph, MSc; A V Geetha, MSc; Dorairaj Prabhakaran, ProfMD; Panniyammakal Jeemon, PhD (Elsevier, 2019)
Summary: Background: Task sharing for the management of hypertension could be useful for understaffed and resource-poor health systems. We assessed the effectiveness of task-sharing interventions in improving blood pressure control among adults in low-income and middle-income countries. Methods: We searched the Cochrane Library, PubMed, Embase, and CINAHL for studies published up to December 2018. We included intervention studies involving a task-sharing strategy for management of blood pressure and other cardiovascular risk factors. We extracted data on population, interventions, blood pressure, and task sharing groups. We did a meta-analysis of randomised controlled trials. Findings: We found 3012 references, of which 54 met the inclusion criteria initially. Another nine studies were included following an updated search. There were 43 trials and 20 before-and-after studies. We included 31 studies in our meta-analysis. Systolic blood pressure was decreased through task sharing in different groups of health-care workers: the mean difference was −5·34 mm Hg (95% CI −9·00 to −1·67, I2=84%) for task sharing with nurses, −8·12 mm Hg (-10·23 to −6·01, I2=57%) for pharmacists, −4·67 mm Hg (-7·09 to −2·24, I2=0%) for dietitians, −3·67 mm Hg (-4·58 to −2·77, I2=24%) for community health workers, and −4·85 mm Hg (-6·12 to −3·57, I2=76%) overall. We found a similar reduction in diastolic blood pressure (overall mean difference −2·92 mm Hg, −3·75 to −2·09, I2=80%). The overall quality of evidence based on GRADE criteria was moderate for systolic blood pressure, but low for diastolic blood pressure. Interpretation: Task-sharing interventions are effective in reducing blood pressure. Long-term studies are needed to understand their potential impact on cardiovascular outcomes and mortality. Funding: Wellcome Trust/DBT India Alliance.